2017
DOI: 10.3389/fmicb.2017.00412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Four Isosphaeraceae Planctomycetes: A Common Pool of Plasmids and Glycoside Hydrolase Genes Shared by Paludisphaera borealis PX4T, Isosphaera pallida IS1BT, Singulisphaera acidiphila DSM 18658T, and Strain SH-PL62

Abstract: The family Isosphaeraceae accommodates stalk-free planctomycetes with spherical cells, which can be assembled in short chains, long filaments, or aggregates. These bacteria inhabit a wide variety of terrestrial environments, among those the recently described Paludisphaera borealis PX4T that was isolated from acidic boreal wetlands. Here, we analyzed its finished genome in comparison to those of three other members of the Isosphaeraceae: Isosphaera pallida IS1BT, Singulisphaera acidiphila DSM 18658T, and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 70 publications
5
31
2
Order By: Relevance
“…However, Planctomycetes have recently been recognized as important producers of bioactive compounds by both in silico genome mining analyses and molecular screening approaches. These analyses revealed the presence of genes related to various pathways for the production of several bioactive molecules, including some antitumor compounds like epothilone (Donadio et al, 2007;Graça et al, 2013;Wang et al, 2014;Graça et al, 2016;Ivanova et al, 2017;Vollmers et al, 2017). It is therefore very promising that several of our Planctomycetes strains isolated from various ecosystems showed significant cytotoxic activity toward the MOLM-13 cells and the human prostatic PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Planctomycetes have recently been recognized as important producers of bioactive compounds by both in silico genome mining analyses and molecular screening approaches. These analyses revealed the presence of genes related to various pathways for the production of several bioactive molecules, including some antitumor compounds like epothilone (Donadio et al, 2007;Graça et al, 2013;Wang et al, 2014;Graça et al, 2016;Ivanova et al, 2017;Vollmers et al, 2017). It is therefore very promising that several of our Planctomycetes strains isolated from various ecosystems showed significant cytotoxic activity toward the MOLM-13 cells and the human prostatic PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the gene encoding the key enzyme for synthesis of N-methylated phosphorus-free ornithine membrane lipids, N-methyltransferase (OlsG), was identified in the genome of Singulisphaera acidiphila DSM 18658 T (Sinac_1600) (24) and later detected in genomes of other members of the family Isosphaeraceae (11). Our analysis revealed that distant homologs of Sinac_1600 are also present in the genomes of Gemmataceae planctomycetes, including F. ruber SP5 T , Zavarzinella formosa A10 T , and Gemmata sp.…”
Section: Chitin As a Source Of C Chitin As A Source Of Nmentioning
confidence: 99%
“…Members of the family Isosphaeraceae are especially abundant in boreal peatlands (9,10). As revealed by recent comparative genomic analysis, these peat-inhabiting planctomycetes possess extremely high but partly hidden glycolytic potential (11) and are capable of degrading various heteropolysaccharides. The ability to degrade fibrous and microcrystalline cellulose, however, has so far been demonstrated only for a single, peat-inhabiting planctomycete from the family Gemmataceae, Telmatocola sphagniphila (12).…”
mentioning
confidence: 99%
“…Members of the order Phycisphaerales and genus Zavarzinella also responded to xylan, while group WD2101 were responsive to cellulose and chitin. Another study by Ivanova et al (2017b) further supported the high glycolytic potential of Planctomycetes. In that study, a comparative genomic analysis of 4 members of the family Isosphaeraceae, namely Isosphaera pallida, Singulisphaera acidiphila, Paludisphaera borealis and the uncharacterized strain SH-PL62S, identified several CAZYmes from major families (GH5, GH13, GH57) as well as potential α-mannosidase, α-rhamnosidase and glucuronyl hydrolase activities.…”
Section: Alpha and Beta Diversitymentioning
confidence: 84%
“…The most abundant bacterial genus in the "heavy" fraction, Singulisphaera, had mostly positive connections, especially with other groups of Planctomycetes, Actinobacteria and Verrucomicrobia, suggesting potential cooperation for metabolizing WH15EPS. Several studies demonstrate that those groups of bacteria have glycolytic and detoxifying capacities, producing several enzymes that could be involved in the degradation of the EPS and resource sharing (Martinez-Garcia et al, 2012;Uhlik et al, 2012;Ivanova et al, 2017b). In addition, no direct correlation was found between Singulisphaera and the EPS producer Granulicella, which suggests that the metabolism of WH15EPS by Singulisphaera and enrichment of the genus did not negatively impact the abundance of Granulicella.…”
Section: Co-occurrence and Active Potential Interactionsmentioning
confidence: 99%